Rural banks (BPRs) have some roles to small industries especially in rural area. The roles of BPRs are very important to develop the small industries because their capitals still limited. But BPRs have some problems to conduct their roles. The objectives of this study were (1) to identify small industries that being client of BPRs in West Sumatra and (2) to analyze the impact of credit to the increasing of small industries performance. Those objectives can be analyzed using descriptive appro - Zednita Azriani; Harianto .; Nunung Nuryartono (Forum Pasca Sarjana, 2008)
Rural banks (BPRs) have some roles to small industries especially in rural area.  The roles of BPRs are very important to develop the small industries because their capitals still limited.  But BPRs have some problems to conduct their roles.  The objectives of this study were (1) to identify small industries that being client of BPRs in West Sumatra and (2) to analyze the impact of credit to the increasing of small industries performance.  Those objectives can be analyzed using descriptive approaches and econometrics in form of small industries model as simultaneous equation.  The result showed that amount of credit that received by small industries was only significant to value small industries but not significant to using labor.  There was no difference between the performance of constructed rural bank’s credit clients and non-constructed rural bank’s credit clients. Key words: credit, rural banks, financial performance, small industries